Using an Technology Readiness Model to Understand Perceived Usefulness of Learning in the Covid-19 Era - Gestiardi, Rivan; Sarwanto, Sarwanto; Chumdari, Chumdari; Maryani, Ika (International Journal of Elementary Education, 2021)
The use of new technology for educators makes it difficult for educators to update existing learning, knowledge skills, and various knowledge. However, the application of technology to the attitude of educators in adopting new technology is joined with the covid-19 pandemic, which requires educators to prepare technology. Technology readiness (TR) becomes a model in preparing technology that characterizes individuals using and adopting new technologies to achieve the desired goals. Perceived usefulness is an essential indicator of the attitude we take in the use of specific technologies. The purpose of this study was to analyze the TR of perceived usefulness in learning in the Covid-19 era. This research focuses on providing a general understanding and awareness of the importance of TR in everyday life. This type of research is quantitative, using univariate analysis and simple linear regression. This research design includes correlational research. The number of samples was 215 students were involved. The data collection tool uses an online questionnaire. The result is that school teacher education students in Yogyakarta have high TR abilities and positively affect perceived usefulness. This research implies that educators or stakeholders realize the importance of TR and technology services by encouraging positive attitudes towards technology to reduce reluctance to use technology.